Two-layer spherical rubber-metal joints and problems of their calculation features - A. S. Kosmodamianskiy; V. I. Vorob'ev; O. V. Izmerov; D. N. Shevchenko; D. Yu. Rasin (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The article analyses the methods for calculating the characteristics of spherical rubber-metal joints. The authors consider a verified calculation model for determining the stiffness characteristics of spherical rubber-metal joints, both single-layer and double-layer.Materials and methods. The researchers used computer modelling and the finite element method to determine the features of the spherical rubber-metal joints. The possibility of neglecting the deformation of the metal parts of the joint for the modelling purposes was substantiated, which enabled to simplify the calculation model. Moreover, the authors proposed the method for measuring the effect of the elastic layer precompression and determined the values of radial stiffness for single-layer and double-layer rubber-metal joints at different hardness of materials, which coincided with the experimental results. Results. As a result, the authors revealed that with a decrease in the thickness of the rubber layer by assessing the rigidity of the joint, its features were significantly affected by the accuracy of setting the Poisson's ratio. A satisfactory convergence of the radial stiffness of the joint found through the modelling and experimental studies was achieved at a Poisson's ratio equal to 0.499999 (the discrepancy is about 5 %, which is less than the technological spread of rigidity during manufacture). The authors also found out that the rigidity of two-layer rubber-metal joints, similar in size and compensatory capacity to those used in the design of domestic locomotives, should be 6.3 times higher than for existing single-layer ones. Such features would reduce the deformation of rubber by loads exsposion during operation and thereby would solve the problems with the reliability of traction motors suspension units.Discussion and conclusion. Due to the fact that the shape of the free surface of the side faces of two-layer rubber-metal joints before assembly should have small radii of the recesses curvature, further research is needed to select the rational geometry of the free surface of the side faces. The researchers got a utility model patent for the proposed design and manufacturing technology of two-layer rubber-metal joints.